Bustos, José Jesús de ( Coord.). Textualización y oralidad, Madrid:Visor libros/Instituto Universitario Menéndez Pidal, 2003,207 pp. [=Biblioteca itlológica hispánica 65]. - Garatea, Carlos (2005)
No contiene resumen